The influence of locus of control, responsibility and job knowledge on employees' organizational commitment at universitas Batam - Muhammad Tommy Arby Rumen; Chablullah Wibisono; Angelina Eleonora Rumengan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Locus of Control (LoC) is an individual's perception of the sources that control events in their lives, which are divided into two main categories: internal and external. Individuals with internal LoC tend to have higher performance because they believe that success is influenced by their own efforts and abilities, while individuals with external LoC believe that the results of their actions are more influenced by external factors that are beyond their control, such as fate, luck, situations, or the power of others. This study aims to examine the effect of Locus of Control, responsibility, and job knowledge on organizational commitment with work motivation as an intervening variable at Universitas Batam. The research method used is a causal model survey with path analysis techniques. The study population was 90 employees of Universitas Batam with census techniques. The results showed that Locus of Control had a significant effect on employee performance. These findings provide strategic recommendations for Universitas Batam in increasing organizational commitment through a deeper understanding of internal factors such as work motivation.